PERAN GURU AGAMA DALAM MEMBINA IMAN PESERTA DIDIK - Munthe, Novlin (STP St. Bonaventura Medan, 2018)
This research aims to describe the role of Catholic religious teachers at Sumbul 1 State High School. This research uses qualitative research methods. Data collection techniques in this research were carried out using observation, interviews and documentation. Next, the data that has been collected is reduced, analyzed and tested for validity by means of source triangulation. The research results show that Catholic religious teachers have carried out their role well through religious teachers as facilitators, motivators, communicators, educators and preachers of the faith, models and exemplars, witnesses of Christian news, and as coaches. This role is carried out by religious teachers in teaching and learning activities and outside of school